PENYELESAIAN SENGKETA BAK BATAS TANAH MENURUT ADAT DAYAK LIMBAI ANTARA PEMILIK TANAH DENGAN PERUSAHAAN KELAPA SAWIT PT. BINTANG PERMATA KHATULISTIWA DI DUSUN LENGKONG SANGSANG DESA SUNGAI SAMPUK KECAMATAN MENUKUNG KABUPATEN MELAWI - NIM. A1012181059, DELVIA (Jurnal Fatwa Hukum, 2021)
Land boundary rights dispute between the land owner and the oil palm company PT. Bintang Permata Khatulistiwa is a dispute that occurred in the hamlet of Lengkong Sansang, Sungai Sampuk Village, the cause of the dispute over land boundary rights, namely the ownership of land boundary rights that are not clear and also taking ownership of land by the Palm Oil Company PT. Bintang Permata Ktulistiwa, where the Company took action by shifting the land boundary rights stake.This study uses an empirical method with a descriptive analysis type approach that describes the situation as it was at the time of the study, and then analyzes it to draw final conclusions. Techniques and data collection tools using direct communication techniques by means of interviewsThat the settlement of land boundary rights disputes for the Limbai Dayak Indigenous Peoples in Lengkong Sansang Hamlet, Sungai Sampuk Village, Menukung District, Melawi Regency was carried out through the Limbai Dayak Customary Head which was resolved by peaceful means, deliberation and kinship based on the Limbai Dayak customary law which has been applied in life In the daily life of indigenous peoples in the Lengkong Sansang Hamlet, Sungai Sampuk Village, Menukung District, Melawi RegencyFactors causing Land Boundary Rights Disputes between Land Owners and Palm Oil Companies Pt. Bintang Permata Khatulistiwa in Lengkong Sansang Hamlet, Sungai Sampuk Village, Menukung District, Melawi Regency, began with the entry of oil palm companies that wanted to occupy or control the land, which resulted in a dispute over land boundary rights.Efforts that can be made by the two disputing parties in overcoming the occurrence of land boundary rights disputes are by reporting the problem of land boundary rights disputes to the Customary Institution which is authorized to resolve and adjudicate cases of land boundary rights disputes between land owners and the PT. Bintang Permata Khatulistiwa in Lengkong Sansang Hamlet, Sungai Sampuk Village, Menukung District, Melawi RegencyKeywords: Dispute, Dayak Limbai, Settlement, Land Boundary Rights.